Trauma-related symptoms in adolescents: the differential roles of sexual abuse and mentalizing - Wais, Marissa; Bégin, Michaël; Sharp, Carla; Ensink, Karin (Frontiers in Psychology, 2024)
Introduction Major gaps remain in our knowledge regarding childhood sexual abuse (CSA) related symptoms in adolescent psychiatric inpatients, as well as potential resilience factors like mentalizing. CSA is a risk factor for the early emergence of borderline personality features, posttraumatic stress, and sexual concerns. Mentalizing, which involves the capacity to understand our reactions and that of others in psychological terms, is a resilience factor for self and interpersonal functioning. The aim of this study was to address knowledge gaps by examining the contributions of CSA and mentalizing in a latent factor composed of borderline personality features, posttraumatic stress, and sexual concerns in a sample of adolescent psychiatric inpatients. We hypothesized that CSA and mentalizing would independently explain the variance in this latent factor. Method Participants were 273 adolescents aged 12–17 recruited from an adolescent inpatient psychiatric clinic. They completed the Reflective Function Questionnaire for Youth (RFQ-Y), the Trauma Symptom Checklist for Children (TSCC), and the Borderline Personality Features Scale for Children (BPFS-C). CSA was assessed using the Child Attachment Interview (CAI), the Computerized Diagnostic Interview Schedule for Children (C-DISC), as well as the Childhood Trauma Questionnaire (CTQ). Results 27.5% of adolescent psychiatric inpatients reported CSA. CSA and mentalizing were independently associated with a latent factor consisting of posttraumatic stress, borderline personality features, and sexual concerns. CSA explained 5.0% and RF explained 16.7% of the variance of the latent factor. When we consider both the unique and the shared contribution of CSA and mentalizing, the model explained 23.0% of the variance of this factor. Discussion CSA and mentalizing independently explained variance in a latent factor constituted of borderline personality features, posttraumatic stress, and sexual concerns. The direct effect of mentalizing was stronger and mentalizing explained comparatively more variance of trauma-related symptoms in adolescent psychiatric inpatients. The findings are consistent with the theory that mentalizing is an internal resilience factor in adolescent psychiatric inpatients. By implication, clinical interventions focused on promoting the development of mentalizing, such as Mentalization Based Treatment, may palliate mental health difficulties manifested by adolescent psychiatric inpatients including those associated with CSA.